On the front line of primary health care: the profile of community health workers in rural Quechua communities in Peru - Zumaran Adriana; Malca Rosa; Brown Angela; Miranda J Jaime (BMC, 2006)
Abstract Objective To describe the profile of community health workers - health promoters, traditional birth attendants and traditional healers - in rural Quechua communities from Ayacucho, Peru. Methods Basic quantitative and qualitative information was gathered as part of a community health project implemented between 1997 and 2002 in 40 Andean communities with information from questionnaires, personal interviews and group discussions. Results The majority of current community health workers are men with limited education who are primarily Quechua speakers undertaking their work on a voluntary basis. Health promoters are mostly young, male, high school graduates. There exists a high drop-out rate among these workers. In contrast, traditional healers and traditional birth attendants possess an almost diametrically opposite profile in terms of age, education and drop-out rates, though males still predominate. At the community level the health promoters are the most visible community health workers. Conclusion It is very important to consider and to be aware of the profile of community health workers in order to provide appropriate alternatives when working with these groups as well as with the indigenous population, particularly in terms of culture, language and gender issues.